Perancangan Pendeteksi Asap Rokok di Ruangan Not Smoking Area pada Bandara Menggunakan Mikrokontroller Berbasis Android - Sabur, Fatmawati; Atmia, Kurniaty (Politeknik Penerbangan Makassar, 2019)
The non-smoking rooms at the airport are crucial. Cigarette smoke is very harmful to health because it contains various pollution substances that can cause a variety of cough diseases, cancer, and other health disorders. There are many ways to minimize the danger of cigarette smoke by making non-smoking stickers/banners and smoking prohibition seminars. However, the way is less effective because there are still some people who do not realize the importance of not smoking in public places and indoor or air-conditioned rooms. The purpose of this research is to design a cigarette smoke detector simulation tool in an indoor and AIR-conditioned room that is displayed through the Dashboard Floor plan Indoor Airport room, using Microcontroller Node MCU equipped ESP8266 Wireless module by using MQTT protocol for Data Communication sensor node to server with system test using black box testing approach or in generally known as test case. The type of this research is experimental research. This research is conducted by conducting trials where mechanical and electronic design for hardware component. Technique or method used is a method of library by collecting some written data both from books, literature, and tutorials as reference material and observe the conditions at Gate 1 of Sultan Hasanuddin Airport. Conclusion based on testing results of cigarette smoke detector is a prototype system of cigarette smoke detection tools can detect smoke of the smoking at the threshold of 650 ppm and provide information related to the location of smoke detection by utilizing a network Internet. So, the airport can detect cigarette smoke easily and to effective smoking ban in a room is AIR-conditioned.